2021
DOI: 10.1177/00332941211012622
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Emotional Processes and Life Satisfaction of Korean Adults With Childhood Abuse Experience According to the Level of Emotional Expressiveness

Abstract: This study evaluates a hypothesized model describing the cognitive and emotional processes of childhood abuse and its influence on life satisfaction and explores the moderating effect of emotional expressivity in Korean young adults. The mediating roles of early maladaptive schema and state anxiety are explored, and the level of life satisfaction is compared according to the emotional expressivity level. A total of 550 young adults completed self-reported questionnaires, including Childhood Trauma Questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…The ndings showed that there signi cant negative relationships between life satisfaction and EMSs including emotional deprivation, social isolation, defectiveness/shame, failure, dependence/incompetence, vulnerability to harm or illness, subjugation, self-sacri ce, emotional inhibition, unrelenting standards/hypercriticalness and insu cient self-control/self-discipline. These ndings are in line with most previous studies [31,32,[93][94][95].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The ndings showed that there signi cant negative relationships between life satisfaction and EMSs including emotional deprivation, social isolation, defectiveness/shame, failure, dependence/incompetence, vulnerability to harm or illness, subjugation, self-sacri ce, emotional inhibition, unrelenting standards/hypercriticalness and insu cient self-control/self-discipline. These ndings are in line with most previous studies [31,32,[93][94][95].…”
Section: Discussionsupporting
confidence: 94%
“…EMS is formed when basic emotional needs are not met (e.g., autonomy, safety, and security) [28]. When EMSs become active, they can lead to several cognitive and behavioural problems [29,30] as well as negatively impact life satisfaction [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some studies have explored relationships between resilience and life satisfaction. For example, a study reported that resilience positively predicted life satisfaction based on a sample of 201 American college students [ 29 ]. A study reported that resilience was positively associated with life satisfaction among 282 Chinese college students [ 30 ].…”
Section: Introductionmentioning
confidence: 99%